A Devaluation Model for a Small Open Economy - Martin F.J. Prachowny (Queen's University, Department of Economics, 1972)
The purpose of this paper is to develop a devaluation model for a small open economy that incorporates the crucial features of non-traded goods, money, and the requirements of portfolio equilibrium. Also, it will be shown in the paper that the exchange rate influences the price level and aggregate output, and therefore it can become a tool of stabilization policy, especially if monetary and fiscal policies are unavailable for this purpose.
Keywords: 330